Pembangunan Hukum Nasional Perspektif Kesetaraan dan Keadilan Gender dalam Lembaga Legislatif - . Baharudin (KEADILAN PROGRESIF, 2012)
Participation woman marginalisation in politics of have implication to at life of and politics  have state to in Indonesia, what is always predominated by men folk. Process of Marginalisation happened continuously, this implication will to lowering of knowledge of woman to general election. Development of national law in is in perpective of equivalence and justice of gerder to fill legislative institute, have to pay attention procedure regulation of peundang of invitation, Party grow cultural conciousness of law of keterwakilan of gender, giving education of politics, besides proposing and specifying Legislative Candidate list. Political Party as according to its function give education of politics to gender  have equivalence dimension to and justice and of revitalisation cultural value of law of mereflsikan confession to woman rights. With capital of is quality of woman can act in national development.